الجهود الاصلاحية للشيخ محمد خير الدين البسكري (1902-1993) - عميار, هناء; عازب احمد, مروة (University of Eloued-جامعة الوادي, 2022)
"يعتبر الشيخ محمد خير الدين من العلماء المصلحين في الجزائر ابان الثورة التحريرية، وقد كان له دور بارز إلى جانب علماء جمعية علماء المسلمين الجزائريين، فهو من المؤسسين الأوائل للجمعية مع الشيخ ابن باديس والشيخ الإبراهيمي وغيرهم. واستمدت الدراسة أهميتها من دور جمعية العلماء المسلمين الجزائريين ضمن الحركة الوطنية الجزائرية من أجل تحرير الوطن، وقيمة عملها المتمثل أساسا في عمل محمد خير الدين المتمثل في أنها نادت باليقظة والإصلاح من جهة، وإعداد جيل جديد يفهم الإسلام فهما صحيحا ويهتم بقضية التربية والتعليم، التي تمثل القاعدة الأساسية لا للتقدم فحسب وإنما للحياة الحرة الكريمة من جهة أخرى. ""Sheikh “Muhammad Khair al-Din” is considered one of the reformed scholars in Algeria during the liberation revolution, and he had a prominent role alongside the scholars of the Association of Algerian Muslim Scholars, as he is one of the first founders of the association with Sheikh Ibn Badis, Sheikh Ibrahimi and others. The study derived its importance from the role of the Association of Algerian Muslim Scholars within the Algerian national movement for the liberation of the country, and the value of its work represented mainly in the work of Muhammad Khair al-Din represented in that it called for vigilance and reform on the one hand, and the preparation of a new generation that understands Islam correctly and cares about the issue of education, which represents The basic rule is not only for progress, but for a free and dignified life on the other hand.
مذكرة ماستر
Keywords: محمد خير الدين، الجهود الاصلاحية.; Muhammad Khair El-Din, reform efforts.